Hollow porous copper particle
Patent Information
- Application Number
- JP2023127214
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-03
- Publication Date
- 2025-02-14
AI Technical Summary
【0012】 本発明は、酸化処理がなされることなく、レーザー吸収性に優れた銅粒子を提供することができる。
Smart Images

Figure 2025022535000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to hollow porous copper particles. [Background technology]
[0002] As electronic devices become smaller and more powerful, copper particles are expected to be used as a material for electronic devices. In recent years, research and development has been conducted into the use of copper powder as a metal material for additive manufacturing (AM), also known as 3D printer technology.
[0003] Among additive manufacturing (AM) technologies, laser-based additive technology is attracting particular attention. In additive manufacturing using lasers, metal powder is sintered or melted and bonded by laser irradiation. However, metal materials with high laser reflectivity, such as copper and aluminum, do not easily absorb the energy of the laser, so in order to sinter or melt and bond metal particles made of these metal materials, it is necessary to irradiate them with a laser of higher energy. As a result, there are difficulties such as higher manufacturing costs due to the high energy of the laser, a more complex configuration of the manufacturing equipment, and the inability to bond metal particles together properly.
[0004] From this perspective, techniques have been sought to improve the laser absorption rate of copper particles.
[0005] Patent Document 1 discloses a technique for improving the laser absorption rate by providing a specific oxide film on the surface of copper powder through oxidation treatment. However, it is not desirable to chemically change copper powder through oxidation treatment or the like to turn it into a state other than metallic copper.
[0006] Patent Document 2 discloses a metal powder for additive manufacturing in which partial sintering due to preheating or the like is suppressed by forming a surface coating. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2018-178239 A [Patent Document 2] Patent Publication No. 7192161 Summary of the Invention [Problem to be solved by the invention]
[0008] Thus, there has been a demand for copper particles that have excellent laser absorbency without the need for oxidation treatment of the copper particles.
[0009] Therefore, an object of the present invention is to provide copper particles that have excellent laser absorbency without being subjected to an oxidation treatment. [Means for solving the problem]
[0010] As a result of extensive research, the present inventors have discovered that the above object can be achieved by the means described below, and have arrived at the present invention.
[0011] Therefore, the present invention includes the following (1): (1) A hollow porous copper particle comprising an outer shell portion disposed outside a hollow portion, the outer shell portion being porous. Effect of the Invention
[0012] The present invention can provide copper particles having excellent laser absorbency without being subjected to an oxidation treatment. [Brief description of the drawings]
[0013] [Figure 1A] FIG. 1A is an SEM image obtained by observing Sample 1 with an SEM. [Figure 1B]Figure 1B shows the automatic detection of particles in the SEM image of Figure 1A using the Analyze Particles function of ImageJ. [Figure 1C] FIG. 1C is a composite image in which the image of FIG. 1B is superimposed on the image of FIG. 1A. [Figure 1D] FIG. 1D is an image showing the default parameter settings of the make binary function of ImageJ (version 1.54d) used for the binarized analysis of SEM images. [Diagram 2] FIG. 2 is a graph showing the particle size distribution measurement results of Sample 1. [Diagram 3] FIG. 3 is an image obtained by observing the sample 1 using a focused ion beam (FIB) device. [Figure 4A] FIG. 4A is a partially enlarged image of the particles surrounded by enlarged area-1 among the particles shown in the image of FIG. [Figure 4B] FIG. 4B is an image in which a circumscribing ellipse and an inscribing ellipse are drawn for the particle in the image of FIG. 4A. [Figure 5A] FIG. 5A is a partially enlarged image of the particles surrounded by enlarged area-2 among the particles shown in the image of FIG. [Figure 5B] FIG. 5B is an image in which a circumscribing ellipse and an inscribing ellipse are drawn for the particle in the image of FIG. 5A. [Figure 6] FIG. 6 is a partially enlarged SEM image of the particle near the upper center of FIG. 1A. [Figure 7] FIG. 7 is a graph showing the results of measuring the laser absorptance at each wavelength for the particles of Sample 1, Sample 2, and Sample 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention will be described in detail below with reference to specific embodiments, but the present invention is not limited to the specific embodiments disclosed below.
[0015] [Hollow porous copper particles] In a preferred embodiment, the hollow porous copper particle of the present invention comprises an outer shell portion disposed outside the hollow portion, and the outer shell portion is porous.
[0016] [Outer shell] In a preferred embodiment, the hollow porous copper particle of the present invention comprises an outer shell portion disposed outside a hollow portion. Since the hollow portion is hollow, it is difficult to express it as a part of the particle, but in the present application, it is referred to as the hollow portion for the purpose of expressing the structure.
[0017] [Porous] In a preferred embodiment, the shell portion disposed outside the hollow portion is porous. In the present application, the shell of the hollow porous copper particle is porous, and a large number of holes and voids are observed in an SEM image of the surface of the shell of the particle. In addition, in the present application, the shell of the hollow porous copper particle is porous, and a large number of voids and through-holes are observed in an FIB image of the cross section of the shell of the particle. The through-hole is a hole in which the void portion is connected from the outer surface of the shell to the inner surface. The present inventor believes that such a porous structure is generated due to the production process of the hollow porous copper particle of the present application.
[0018] [Agglomerated layer of primary particles] In a preferred embodiment, the shell portion disposed outside the hollow portion is made of an agglomerated layer of primary particles. The term "primary particles" is used as an expression indicating the relative role of the hollow porous copper particles of the present application, that is, that the particles are secondary particles made of small particles called primary particles. In the present application, the shell of the hollow porous copper particles is an agglomerated layer of primary particles, and in an SEM image of the surface of the particle's shell, it is observed that the shell is made of agglomerated primary particles. In the present application, the shell of the hollow porous copper particles is an agglomerated layer of primary particles, and in an FIB image of the cross section of the particle's shell, it is observed that the shell is made of agglomerated primary particles.
[0019] [Primary particle size] In a preferred embodiment, the particle size of the primary particles of the aggregate layer of the outer shell portion can be, for example, in the range of 0.01 to 0.09 μm, preferably in the range of 0.02 to 0.09 μm, preferably in the range of 0.03 to 0.09 μm, preferably in the range of 0.04 to 0.09 μm, or in the range of 0.02 to 0.08 μm, preferably in the range of 0.03 to 0.08 μm, preferably in the range of 0.04 to 0.08 μm, or in the range of 0.02 to 0.07 μm, preferably in the range of 0.03 to 0.07 μm, preferably in the range of 0.04 to 0.07 μm, or in the range of 0.02 to 0.06 μm, preferably in the range of 0.03 to 0.06 μm, preferably in the range of 0.04 to 0.06 μm. The particle size of the primary particles of the aggregate layer can be measured by the procedure described later in the Examples.
[0020] In a preferred embodiment, the primary particles of the outer shell agglomerate layer may have a shape, for example, of a sphere, a spheroid, an oblate spheroid, an oblong spheroid, or a bell-shaped shape.
[0021] [Thickness of outer shell] In a preferred embodiment, the thickness of the shell portion disposed outside the hollow portion can be, for example, in the range of 0.1 to 0.4 μm, alternatively 0.15 to 0.4 μm, alternatively 0.2 to 0.4 μm, alternatively 0.1 to 0.35 μm, alternatively 0.15 to 0.35 μm, alternatively 0.2 to 0.35 μm, alternatively 0.25 to 0.35 μm, alternatively 0.1 to 0.3 μm, alternatively 0.15 to 0.3 μm, alternatively 0.2 to 0.3 μm, alternatively 0.25 to 0.3 μm. The thickness of the shell portion can be measured by the procedure described later in the Examples.
[0022] [Particle Shape] In a preferred embodiment, the hollow porous copper particles of the present invention can have a spherical outer shape. Generally, even particles called copper particles are often not necessarily spherical in outer shape, but as shown in the examples described below, in a preferred embodiment, the hollow porous copper particles of the present invention can have a spherical outer shape with a uniform size.
[0023] In a preferred embodiment, the hollow porous copper particles of the present invention have an outer shape that is a well-ordered sphere, and the aspect ratio measured in the examples described later can be, for example, in the range of 1.000 to 1.300, or 1.000 to 1.250, or 1.000 to 1.200, or 1.000 to 1.150, or 1.000 to 1.100.
[0024] In a preferred embodiment, the hollow porous copper particles of the present invention have an outer shape that is a highly regular sphere, and the average aspect ratio measured in the examples described later can be, for example, in the range of 1.000 to 1.300, or in the range of 1.000 to 1.250, or in the range of 1.000 to 1.200, or in the range of 1.000 to 1.150.
[0025] [Particle size] In a preferred embodiment, the hollow porous copper particles of the present invention have an average particle size D50 in the range of, for example, 1 to 3 μm, alternatively 1 to 2.5 μm, alternatively 1 to 2 μm, alternatively 1.5 to 2 μm, or alternatively 1.6 to 1.9 μm.
[0026] In a preferred embodiment, the particle size of the hollow porous copper particles of the present invention can be, for example, an average particle size D90 in the range of 1 to 4 μm, alternatively in the range of 1 to 3.5 μm, alternatively in the range of 1 to 3 μm, alternatively in the range of 1.5 to 4 μm, alternatively in the range of 1.5 to 3.5 μm, alternatively in the range of 1.5 to 3 μm, alternatively in the range of 2 to 4 μm, alternatively in the range of 2 to 3.5 μm, alternatively in the range of 2 to 3 μm, alternatively in the range of 2.5 to 4 μm, alternatively in the range of 2.5 to 3.5 μm, alternatively in the range of 2.5 to 3 μm, or alternatively in the range of 2.6 to 2.9 μm.
[0027] In a preferred embodiment, the particle size of the hollow porous copper particles of the present invention can be, for example, an average particle size D10 in the range of 0.5 to 3 μm, alternatively in the range of 0.5 to 2.5 μm, alternatively in the range of 0.5 to 2 μm, alternatively in the range of 0.5 to 1.5 μm, alternatively in the range of 0.7 to 3 μm, alternatively in the range of 0.7 to 2.5 μm, alternatively in the range of 0.7 to 2 μm, alternatively in the range of 0.7 to 1.5 μm, alternatively in the range of 0.7 to 1.3 μm, alternatively in the range of 0.9 to 1.5 μm, or alternatively in the range of 0.9 to 1.3 μm.
[0028] In a preferred embodiment, the particle size of the hollow porous copper particles of the present invention is determined by the span, i.e., the following formula: ("Average particle diameter D90" - "Average particle diameter D10") / "Average particle diameter D50" The value represented by the above formula can be, for example, 1.8 or less, preferably 1.7 or less, preferably 1.6 or less, preferably 1.5 or less, preferably 1.4 or less, preferably 1.3 or less, preferably 1.2 or less, preferably 1.1 or less, preferably 1.0 or less, preferably 0.99 or less, preferably 0.98 or less, preferably 0.97 or less, preferably 0.96 or less, preferably 0.95 or less, preferably 0.94 or less. The smaller the value of the span represented by the above formula, the more preferable it is, and there is no particular restriction on the lower limit, but it can be, for example, 0.01 or more, or 0.05 or more, or 0.1 or more, or 0.2 or more, or 0.3 or more, or 0.4 or more, or 0.5 or more.
[0029] [purity] In a preferred embodiment, the hollow porous copper particles of the present invention can be copper particles of high purity depending on the purity of the copper sulfate starting material, for example, a purity of 99% by mass or more, preferably a purity of 99.9% by mass or more.
[0030] [Laser absorption rate] In a preferred embodiment, the hollow porous copper particles of the present invention have excellent laser absorptivity.
[0031] According to the study by the present inventors conducted prior to the present invention, generally, the smaller the particle size of copper particles, the higher the laser absorptivity. However, as shown in the examples described later, the hollow porous copper particles of the present invention have a higher laser absorptivity than copper particles having a larger particle size. That is, the excellent laser absorptivity of the hollow porous copper particles of the present invention is a large value that far exceeds the degree of laser absorptivity predicted from the particle size.
[0032] According to the study by the inventors conducted prior to the present invention, the laser absorptivity of copper particles generally drops dramatically when the laser wavelength is in the range of 500 nm to 650 nm, even in the case of copper particle products intended for laser shaping. However, the wavelength of fiber lasers expected for laser shaping is in the range of approximately 1000 nm to 1100 nm due to advantages such as high beam quality, high light conversion efficiency, high output, high reliability, and high maintainability. Therefore, copper particles that do not drop in laser absorptivity and maintain high laser absorptivity up to the range of 1000 nm to 1100 nm have been required for laser shaping. The hollow porous copper particles of the present invention are a product that has been long sought after because they maintain a high absorptivity for laser light in the wavelength range of 1000 nm to 1100 nm.
[0033] In a preferred embodiment, the hollow porous copper particles of the present invention can have an absorptance for laser light having a wavelength in the range of 1000 nm to 1100 nm of, for example, 75% or more, or 76% or more, or 77% or more, or 78% or more, or 79% or more, or 80% or more, or 81% or more, or 82% or more.
[0034] [Laser additive manufacturing] In a preferred embodiment, the present invention also relates to a laser additive manufacturing agent comprising the hollow porous copper particles described above, and to a powder composition for laser additive manufacturing comprising the hollow porous copper particles described above.
[0035] In a preferred embodiment, the present invention also relates to the use of the hollow porous copper particles described above as a laser additive manufacturing agent.
[0036] In a preferred embodiment, the present invention also relates to a method for producing a laser-layered additive manufacturing object, which includes a step of irradiating laser light to the hollow porous copper particles described above; a method for producing a laser-layered additive manufacturing object, which includes a step of irradiating laser light to a laser-layered additive manufacturing agent comprising the hollow porous copper particles described above; and a method for producing a laser-layered additive manufacturing object, which includes a step of irradiating laser light to a powder composition for laser-layered additive manufacturing comprising the hollow porous copper particles described above.
[0037] In a preferred embodiment, in the step of irradiating with laser light, the wavelength of the irradiated laser light can be in the range of 1000 nm to 1100 nm.
[0038] [Preferred embodiment of the present invention] As a preferred embodiment, the present invention includes the following (1) and the following: (1) A hollow porous copper particle comprising an outer shell portion disposed outside a hollow portion, the outer shell portion being porous. (2) The hollow porous copper particles according to (1), wherein the outer shell portion is composed of an agglomerated layer of primary particles. (3) The hollow porous copper particles according to (1), having an average particle size D50 in the range of 1 to 3 μm. (4) The hollow porous copper particles according to (1), wherein the value of ("average particle diameter D90" - "average particle diameter D10") / "average particle diameter D50" is 1.8 or less. (5) The hollow porous copper particles according to (1), wherein the thickness of the outer shell is in the range of 0.1 to 0.4 μm. (6) The hollow porous copper particles according to (1), wherein the primary particle diameter of the agglomerated layer of the outer shell portion is in the range of 0.01 to 0.09 μm. (7) The hollow porous copper particles according to (1), wherein the outer shape of the particles is spherical. (8) The hollow porous copper particles according to (1), having an absorptivity of 75% or more for laser light having a wavelength in the range of 1000 nm to 1100 nm. (9) A laser additive manufacturing agent comprising the hollow porous copper particles according to any one of (1) to (8). (10) A powder composition for laser layered manufacturing, comprising the hollow porous copper particles according to any one of (1) to (8). (11) Use of the hollow porous copper particles according to any one of (1) to (8) as a laser additive manufacturing agent. (12) A method for producing a laser layered product, comprising the step of irradiating a hollow porous copper particle according to any one of (1) to (8) with laser light. (13) The method for producing a laser layered object according to (12), wherein the wavelength of the irradiated laser light is in the range of 1000 nm to 1100 nm. EXAMPLES
[0039] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the examples illustrated below.
[0040] [Experimental Example 1: Production of spherical porous copper particles] [Preparation of reagents] CuSO 4 Solution preparation: Upinog CuSO 4 5H 2 Weigh out 19.7 g of O (JX Metals, high-purity copper sulfate, product name: Upinogu, purity 99% or more by mass), and add pure water to make the total volume 240 ml. 4 A solution was prepared: CuSO 4 Dissolution and volumetric adjustment were carried out at 30°C.
[0041] Preparation of pH adjustment solution: A pH adjustment solution was prepared by diluting a 50% NaOH aqueous solution to 1 / 5.
[0042] Preparation of reducing solution: A reducing solution was prepared by diluting 1.2 g of hydrazine with pure water to 80 ml.
[0043] Preparation of hydrazine + gum arabic solution: 1.2 g of hydrazine was diluted with pure water to 400 ml, and 0.1 g of gum arabic was added to prepare a hydrazine + gum arabic solution.
[0044] Preparation for addition: The tube pump was set, and a pH meter and ORP meter were set in the bath to prepare for addition.
[0045] [Primary pH adjustment] pH adjustment: CuSO 4 The solution was adjusted to pH 5.0 with aqueous NaOH.
[0046] [First reduction] Cuprous oxide reaction: The reducing solution is CuSO 4 The solution was added at a rate of 13.5 ml / min and reacted.
[0047] After the addition was completed, the mixture was kept at 30°C for 1 hour. This carried out the primary reduction, and a slurry of spherical cuprous oxide particles was obtained. A portion of the obtained slurry was sampled, washed with water, dried, and observed by SEM.
[0048] The spherical particles were confirmed by SEM observation under the following conditions: JEOL JSM-7000F Field Emission Scanning Electron Microscope Accelerating voltage: 5.00 kV Filament current 2.18A Extraction voltage: 3.00kV Emission current: 81.40μA PMT link: ON Vacuum Pumping System SIP-1:3.2E-008Pa SIP-2:3.3E-007Pa Vacuum exhaust code: 51FE0000 Penning vacuum gauge: 9.63E-005Pa Sample holder: 2-inch wafer holder
[0049] [Secondary pH adjustment] The temperature of the slurry of spherical cuprous oxide particles produced by the primary reduction was raised to 50°C.
[0050] pH adjustment: An aqueous NaOH solution was added to a slurry of spherical cuprous oxide particles heated to 50° C. to adjust the pH to 12.0.
[0051] [Secondary reduction] Reduction reaction: The hydrazine + gum arabic solution was added at a rate of 6.67 ml / min to the slurry of spherical cuprous oxide particles after pH adjustment, and the reaction was allowed to proceed.
[0052] After the addition was completed, the mixture was kept at 50° C. for 3 hours, then naturally cooled to a temperature at which work was possible, and the cake was recovered by filtration using filter paper.
[0053] Washing: The cake recovered by filtration was dissolved in 200 ml of pure water and then filtered through filter paper. This procedure was repeated three times. The cake obtained by washing was recovered.
[0054] The resulting cake is spread on a tray and 2 The copper powder was obtained by drying at 70° C. in a nitrogen atmosphere. The obtained copper powder was subjected to the following analysis as Sample 1 without being subjected to a crushing operation or a classification operation.
[0055] [Experimental Example 2: Analysis of spherical porous copper particles]
[0056] [Observation by SEM] The obtained copper powder (sample 1) was observed by SEM. The conditions of SEM observation were the same as those of the SEM observation of the cuprous oxide spherical particles described above. The obtained SEM image is shown in Figure 1A.
[0057] From the SEM images, the particles of Sample 1 obtained were spherical particles with a shape close to a perfect sphere, had extremely high particle size uniformity, and all particles had a surface that appeared to be porous.
[0058] From the SEM images, the circularity of the particles was calculated using the following procedure and software. SEM images (Figure 1A) were analyzed using ImageJ (version 1.54d). First, the SEM image file was binarized using the make binary function of ImageJ. The iterations value was set to 1. The count value was set to 1. Unless otherwise specified, the parameter settings were default. The default parameter settings of the make binary function of ImageJ (version 1.54d) used for the analysis of the binarization of SEM images are shown in Figure 1D. Next, the particle outlines were made clearer using the fill holes function. Next, this image was saved and measurable particles were selected. Particles were selected by selecting particles whose entirety was exposed on the front side of the screen and whose parts were not hidden behind adjacent particles, even if only partially, and erasing the other particles. In addition, when the outermost layers of multiple adjacent particles appeared to be fused, the image was processed so that each particle was recognized as a single particle. For the images processed in this way, particles with a diameter of 0.1 μm or more were automatically detected using the Analyze Particles function. 43 particles were automatically detected in the field of view. An image showing how the particles were automatically detected is shown in Figure 1B. The measurements for the automatically detected particles are shown in Table 1.
[0059] A composite image in which the image in Fig. 1B is superimposed on the image in Fig. 1A is shown in Fig. 1C. As shown in Fig. 1C, the particles measured by the automatic detection were the particles located in the foreground of the screen and were the valid targets for measurement.
[0060] The results obtained are shown in Tables 1-1 and 1-2 below.
[0061] [Table 1-1]
[0062] [Table 1-2]
[0063] In Tables 1-1 and 1-2, the area values are the values of the area of each particle projected as a plane in the image.
[0064] In Tables 1-1 and 1-2, the Feret diameter (maximum diameter) value is the distance (maximum caliper length) of the longest line (line segment) among the lines connecting any two points on the boundary line of the outer periphery of the selected particle.
[0065] In Tables 1-1 and 1-2, the minimum diameter value is the distance (minimum caliper diameter) of the shortest straight line (line segment) among the straight lines connecting any two points on the boundary line of the outer periphery of the selected particle.
[0066] In Tables 1-1 and 1-2, the aspect ratio is a value automatically calculated by the above-mentioned Analyze Particles function operation, and is the value obtained by dividing the length of the major axis of the fitted ellipse by the length of the minor axis. In Tables 1-1 and 1-2, 90% or more of the aspect ratios are less than 1.2, which indicates that many particles have a shape close to a sphere. Also, some particles, such as particle number 11, are made up of multiple secondary particles that have aggregated together.
[0067] As shown in Tables 1-1 and 1-2, the particles of the obtained copper powder (sample 1) had an aspect ratio close to 1 and an outer shape that was very nearly circular, without any external processing such as atomization.
[0068] [Measurement of particle size distribution] Regarding the particle size distribution of the obtained copper powder (sample 1), the laser diffraction particle size distribution was measured under the following conditions. Measuring equipment: Laser diffraction particle size distribution analyzer (Mastersizer 3000, Malvern Panalytical) Dispersants: About 1 L of a 0.2 mass % aqueous sodium hexametaphosphate solution was heated to about 50 to 60° C. in a hot bath. Measurement sample preparation: A small amount of Sample 1 was taken and dispersed in about 5 cc of an aqueous solution of sodium hexametaphosphate to prepare a measurement sample. Measurement operation: The dispersion unit of the device was filled with the heated dispersant and stirred while keeping it at 40°C. Next, the measurement sample prepared above was gradually dropped into the dispersant placed in the dispersion unit of the device while stirring and ultrasonic irradiation were performed. During this time, the dispersion was allowed to proceed while measuring the scattering intensity. When the scattering intensity exceeded 6% as the dispersion proceeded, it was confirmed that the scattering intensity remained within the range of 6-8% for 10 minutes, and then the measurement was started. This measurement was performed 10 times for sample 1, and D10 (10% particle size), D50 (50% particle size), and D100 (100% particle size) were calculated, as shown below. D10: 1.094[μm] D50: 1.737[μm] D100: 4.13 [μm] Standard deviation: 0.233
[0069] [Table 2]
[0070] In Table 2, RSD is the relative standard deviation.
[0071] The span, i.e., the value of ("average particle size D90" - "average particle size D10") / "average particle size D50", was 0.9332.
[0072] The results of the particle size distribution measurement showed that the copper particles (sample 1) produced in Experimental Example 1 had a high degree of uniformity in particle size.
[0073] Figure 2 shows a graph of the particle size distribution measurement results for Sample 1. This graph shows the measured values of 10 measurements taken on the slurry of Sample 1, superimposed on each other. The horizontal axis is particle size [μm], and the vertical axis is the volume ratio (%) equivalent to that particle size. As shown in the graph in Figure 2, it was found that the copper particles of Sample 1 have a high degree of uniformity in particle size.
[0074] [Observation by FIB] Sample 1 was observed using a focused ion beam (FIB) device under the following conditions. The images obtained are shown in Figures 3, 4A, and 5A. Partially enlarged views of the particles shown in Figure 3 are shown in Figures 4A and 5A. Device name: SMI3050SE manufactured by SII NanoTechnology (now Hitachi High-Tech) Observation conditions: Ion species Ga+ Ion accelerating voltage: 30kV Observation angle: 55° from the sample surface (35° from the sample normal direction)
[0075] The image in FIG. 4B was created by performing the following operations on the particle shown in FIG. 4A: The image in Figure 4A was analyzed using ImageJ (version 1.54d). First, the image file in Figure 4A was binarized using the make binary function of ImageJ. The iterations value was set to 1. The count value was set to 1. Unless otherwise specified, the parameter settings were set to the default values. For the obtained binarized image file, an ellipse circumscribing the target particle and an ellipse inscribing the target particle were drawn using an image editing software (Microsoft 365, PowerPoint, version 2208). The circumscribing ellipse was placed so that it passed through the average position of the unevenness of the outer surface of the target particle's outer shell. When determining the average position, convexities that were considered to be irregular beyond the normal level of unevenness were excluded from the convexities on the surface, and concaves that were considered to be part of a through hole beyond the normal level of unevenness were excluded, so that the area of the concaves and convexities of the surface unevenness were as equal as possible. The inscribing ellipse was placed so that it passed through the average position of the unevenness of the inner surface of the outer shell of the target particle. Since there are some parts inside the outer shell that exist in the depth direction of the image and do not form part of the cross section of the thickness of the outer shell, these parts were excluded to determine the position of the inner surface of the outer shell. As a result, the ellipses drawn were similar in that the ellipse circumscribing the particle and the ellipse inscribing it were ellipses with the same center point. The distances corresponding to the difference in the radii of the circumscribing ellipse and the inscribing ellipse were measured using the measure function of ImageJ at positions (3), (4), (5), and (6) in Figure 4B. The measurements were performed using the bar at the bottom right of the image as the reference. In addition, the distances corresponding to the major and minor axes of the circumscribing ellipse were similarly measured at positions (1) and (2) in Figure 4B. The measurement results are summarized in Table 3. During measurement, particles are measured by circumscribing and inscribing an ellipse, and the cross section of the particle is observed as if it had an elliptical shape. However, as shown in the SEM image in Figure 3, for theoretical reasons, observation with FIB is performed from an oblique upward direction, so even if the cross section of the particle is actually circular, the observed shape is an ellipse.Therefore, the more reliable value for the thickness of the particle's outer shell is the measured value at the left and right positions on the image ((5) and (6) in Figure 4B), rather than the measured value at the top and bottom positions on the image ((3) and (4) in Figure 4B).
[0076] The lengths indicated by the double-headed arrows of each number in Fig. 4B are shown in Table 3 below. Although each number in Fig. 4B is shown as a circled number, in Table 3 it is shown as a number in parentheses.
[0077] [Table 3]
[0078] The image shown in FIG. 5B is obtained by performing the same operations on the particle shown in FIG. 5A as those performed on the particle shown in FIG. 4A.
[0079] The lengths indicated by the double-headed arrows of each number in Fig. 5B are shown in Table 4 below. Although each number in Fig. 5B is shown as a circled number, in Table 4 it is shown as a number in parentheses.
[0080] [Table 4]
[0081] As shown by these results, the typical shape of the particles of sample 1 was found to be a hollow-structured particle with an outer shell of about 0.3 μm in thickness. In addition, as observed from the image, it was found that this outer shell was formed by the aggregation of many primary particles. In other words, it was found that this hollow-structured particle was a secondary particle formed by the aggregation of many primary particles. From the range observed from the image, these primary particles had a particle size in the range of approximately 0.05 to 0.2 μm. For these primary particles, the maximum caliper length (Ferret diameter) was observed and used as the particle size of the primary particle. In addition, from the cross-sectional image, it was observed that the outer shell had many through holes penetrating the outside and inside of the particle, and from this, it was found that this particle had a shape that could be said to be porous.
[0082] [Primary particle size] FIG. 6 shows an enlarged SEM image of the particle near the top center of FIG. 1A. A large number of primary particles constituting the secondary particle were observed on the surface of the secondary particle in the center of FIG. 6. Many of these primary particles were observed to have a shape close to spherical. Among these primary particles, particles with relatively clear outer diameter contours were selected, and the particle size of many of the primary particles was found to be in the range of 0.04 to 0.06 μm. For these primary particles, the maximum caliper length (Ferret diameter) was observed and used as the particle size of the primary particle.
[0083] [Experimental Example 3: Comparative analysis of spherical porous copper particles] [Laser absorption measurement] The laser absorptivity of Sample 1 was measured under the following conditions using a spectrophotometer. Since typical laser-based modeling uses a fiber laser with a wavelength of about 1060 nm, the reflectivity was measured in a range of wavelengths that included the wavelength of 1060 nm. Manufacturer: Shimadzu Corporation Device name: Spectrophotometer (MPC-3100, using powder holder) Measurement wavelength: 300~1500mm Slit width: 20 nm Reference:BaSO 4 Measurement property: Reflectance Absorption rate (%) = 1 - (Reflectance rate (%))
[0084] The results are shown in Figure 7. The measurements of Samples 2 and 3 in Figure 7 are as described below.
[0085] The absorptivity values for representative wavelengths in the graph of Figure 7 are summarized in Table 5. The absorptivity ratios of the samples at representative wavelengths, i.e., [Sample 1 / Sample 2] and [Sample 1 / Sample 3], are summarized in Table 6.
[0086] [Table 5]
[0087] [Table 6]
[0088] [Measurement of TAP density, etc.] The BET specific surface area, BET diameter, and TAP density of this hollow Cu powder (sample 1) were measured under the following conditions and procedures.
[0089] The tapped bulk density (TAP density) of copper powder was measured using a powder tester PT-X-2 manufactured by Hosokawa Micron Corporation in accordance with JIS Z2512:2012. Specifically, copper powder that had passed through a sieve with 710 μm openings while being vibrated with an amplitude of 1.5 mm was then passed through a 10 cm 3 The copper powder was poured directly into a stainless steel cup with a capacity of 1000 and filled until it overflowed from the stainless steel cup with the guide. Then, tapping was started with the tapping number set to 1000, stroke to 18 mm, and tapping speed to Normal. After tapping, the guide was removed from the stainless steel cup, the opening of the stainless steel cup was scraped off with a scraper to remove excess copper powder, and the weight was measured on a balance and the content was measured at 10 cm. 3 The packed bulk density was calculated from the weight of the copper powder in a stainless steel cup having a capacity of 1.
[0090] The BET specific surface area of copper powder was measured in accordance with JIS Z8830:2013 using a BELSORP-mini II from Microtrack-Bell Co., Ltd. A 3g sample of copper powder was degassed for 5 hours at 70°C in a vacuum with an absolute pressure of 10 Pa or less, and then the nitrogen adsorption isotherm was measured by the static volumetric method. The results were analyzed by the BET method to calculate the BET specific surface area.
[0091] The BET diameter was calculated from the BET specific surface area and density, assuming that the particles are spherical, according to the standard method using the following formula: BET diameter: D(μm)=6 / [density(g / cm 3 ) × BET specific surface area (m 2 / g)]
[0092] The BET specific surface area, BET diameter, TAP density, D50 (50% particle diameter), and D100 (100% particle diameter) of the hollow Cu powder (sample 1) are summarized in Table 7.
[0093] [Table 7]
[0094] As shown in Table 7, the BET diameter of sample 1 was calculated to be 0.15 μm. The BET diameter value of sample 1 was much smaller than the actually measured values of D10 (10% particle diameter), D50 (50% particle diameter), and D100 (100% particle diameter). Furthermore, the BET diameter value of sample 1 was much smaller than the BET diameter of sample 2, which was smaller than sample 1, for example in terms of D50.
[0095] [Measurement of copper fine powder and AM copper powder] As Comparative Example Sample 2, copper fine powder (1 μm product, purity 99.99% by mass, manufactured by Kojundo Chemical Laboratory Co., Ltd.) was prepared. As Comparative Example Sample 3, surface-treated gas atomized copper powder (AM copper powder, purity 99.99% by mass) was prepared in accordance with the procedure of Example 1 of Patent Document 2 (Japanese Patent No. 7192161). These Samples 2 and 3 were measured in the same manner as Sample 1. The results obtained are as shown in FIG. 7, Table 7, Table 5, and Table 6.
[0096] Incidentally, the BET specific surface area of the AM copper powder (sample 3) was not measured because the particle size was significantly different.
[0097] [Comparative analysis results of spherical porous copper particles] As shown in FIG. 7, the hollow Cu powder (sample 1) has superior laser absorptivity over the entire range of measured wavelengths compared to the comparative AM copper powder (sample 3), as shown in Tables 5 and 6.
[0098] As shown in FIG. 7, the hollow Cu powder (sample 1) has a larger particle size than the comparative copper fine powder (sample 2), but is actually superior in laser absorptivity over the entire range of measured wavelengths, as shown in Tables 5 and 6.
[0099] Fiber lasers are known to have excellent advantages such as high beam quality, high light conversion efficiency, high output, high reliability, and high maintainability. The wavelength of this fiber laser is in the range of approximately 1000 nm to 1100 nm. In this fiber laser wavelength band, the main cause of technical difficulties in copper metal 3D printers is the high reflection of metallic copper. However, it was found that the hollow copper particles according to the present invention exhibit 1.55 to 1.53 times the absorbency of conventional copper fine powder in this wavelength range, and 6.67 to 7.09 times the absorbency of conventional AM copper powder. The present invention is a valuable invention that breaks through the technical difficulties of copper metal 3D printers to date. [Industrial Applicability]
[0100] According to the present invention, copper particles having excellent laser absorbency can be produced. The present invention is an industrially useful invention.
Claims
1. A hollow porous copper particle comprising an outer shell portion disposed outside a hollow portion, the outer shell portion being porous.
2. The hollow porous copper particle according to claim 1 , wherein the outer shell portion is composed of an aggregate layer of primary particles.
3. The hollow porous copper particles according to claim 1, having an average particle size D50 in the range of 1 to 3 μm.
4. The hollow porous copper particles according to claim 1, wherein the value of ("average particle diameter D90" - "average particle diameter D10") / "average particle diameter D50" is 1.8 or less.
5. The hollow porous copper particles according to claim 1, wherein the thickness of the outer shell is in the range of 0.1 to 0.4 μm.
6. The hollow porous copper particles according to claim 1, wherein the particle size of the primary particles of the agglomerated layer of the outer shell portion is in the range of 0.01 to 0.09 μm.
7. The hollow porous copper particles according to claim 1, wherein the particle has a spherical outer shape.
8. The hollow porous copper particles according to claim 1, having an absorptivity of 75% or more for laser light having a wavelength in the range of 1000 nm to 1100 nm.
9. A laser additive manufacturing agent comprising the hollow porous copper particles according to any one of claims 1 to 8.
10. A powder composition for laser layered manufacturing comprising the hollow porous copper particles according to any one of claims 1 to 8.
11. Use of the hollow porous copper particles according to any one of claims 1 to 8 as a laser additive manufacturing agent.
12. A method for producing a laser layered product, comprising: irradiating the hollow porous copper particle according to any one of claims 1 to 8 with laser light.
13. The method for producing a laser layered object according to claim 12, wherein the wavelength of the irradiated laser light is in the range of 1000 nm to 1100 nm.
Citation Information
Patent Citations
Copper powder, manufacturing method therefor, and manufacturing method of solid molded article
JP2018178239A
Copper alloy powder having Si coating and method for producing the same
JP7192161B2
Cited By
Hollow copper powder preparation method based on multi-section continuous flow reaction
CN121289495A